Optimization of Lahor Tourism Area Retribution in Blitar District - Susilo; Nayaka Artha Wicesa; Citra Rahayu Indraswari; Rahmat Nur Khairy (Jurnal Informatika Ekonomi Bisnis, 2026)
One of the sectors with strong potential to increase Blitar Regency’s Regional Own Revenue is the Lahor Tourism Area. Retribution income from this area contributes significantly to the total retribution income, yet remains under-optimized due to internal and external challenges such as monitoring weaknesses, technical issues in collection, and competing destinations. This study applies a novel methodological approach by combining micro-level revenue estimation based on vehicle sampling with SWOT analysis to assess potential revenue and formulate optimization strategies. The findings reveal that the potential retribution revenue reaches IDR 2.89 billion per year, far exceeding actual collections, and that the management condition is classified under the PRIMA category. This explicit methodological novelty contributes to the literature on local revenue and tourism levy optimization by demonstrating how micro-estimation techniques can be systematically integrated with strategic analysis. In practical terms, the results provide policy implications for the Blitar Regency Government in designing more effective and transparent retribution management systems.